Obstructive Sleep Apnea and Driving: A Canadian Thoracic Society and Canadian Sleep Society Position Paper. Issue 2 (2014) - Ayas, Najib; Skomro, Robert; Blackman, Adam; Curren, Kristen; Fitzpatrick, Michael; Fleetham, John; George, Charles; Hakemi, Tom; Hanly, Patrick; Li, Christopher; Morrison, Debra; Series, Frédéric
Abstract : Individuals with obstructive sleep apnea (OSA) experience sleep fragmentation and poor sleep quality that results in daytime sleepiness, which impairs performance during driving and leads to an increased risk for collisions. Not surprisingly, observational studies have shown that patients with OSA experience a two- to 10-fold higher risk for collision compared with healthy controls. Although treatment would clearly mitigate these risks, there is no current Canadian position on driving and OSA. This article, the first Canadian position statement addressing the issue, provides an overview of provincial regulations and proposes recommendations with regard to driving in patients with OSA. Untreated patients with obstructive sleep apnea (OSA) are at increased risk for motor vehicle collisions; however, it is unclear how this should be translated into fitness-to-drive recommendations. Accordingly, the Canadian Thoracic Society (CTS) Sleep Disordered Breathing Clinical Assembly and the Canadian Sleep Society (CSS) assembled a CTS-CSS working group to propose recommendations with regard to driving in patients with OSA. Recommendations for assessing fitness to drive in noncommercial drivers: 1. Severity of OSA alone is not a reliable predictor of collision risk and, therefore, should not be used in isolation to assess fitness to drive; 2. The severity of sleep apnea should be considered in the context of other factors to assess fitness to drive; 3. The decision to restrict driving is ultimately made by the motor vehicle licensing authority; however, they should take into account the information and recommendations provided by the sleep medicine physician and should follow provincial guidelines; 4. For patients prescribed continuous positive airway pressure (CPAP) therapy, objective CPAP compliance should be documented. Efficacy should also be documented in terms of reversing the symptoms and improvement in sleep apnea based on physiological monitoring; 5. For patients treated with surgery or an oral appliance, verification of adequate sleep apnea treatment should be obtained; and 6. A driver diagnosed with OSA may be recertified as fit to drive based on assessment of symptoms and demonstrating compliance with treatment. The assessment should be aligned with the provincial driver's license renewal period. Commercial vehicles: Assessment of fitness to drive should be more stringent for patients operating commercial vehicles. In general, the CTS-CSS working group was in agreement with the Medical Expert Panel recommendations to the Federal Motor Carrier Safety Administration in the United States; these recommendations were adapted for Canadian practitioners.